KEBEBASAN BERAGAMA DALAM AJARAN PAUS YOHANES PAULUS II - Neles Tebay (Studia Philosophica et Theologica, 2008)
Religious freedom has become a common theme within the context of international affairs. Given the religiously motivated conflicts and tensions taking place in different parts of the World today, it is necessary to reflect on the importance of religious freedom. The Pope John Paul II defended the importance and necessity of respecting religious freedom, for as proclaimed by the Second Vatican Ecumenical Council, “the human person has a right to religious freedom”. The Pope believes that respect for religious freedom is a touchstone for the observance of the other fundamental rights, a foundation for peace, a cornerstone of the structure of human rights, and one of the pillars of democratic society. This article intends to explore the Pope’s concept of religious freedom, as articulated in his teachings, including the source and foundation of religious freedom, human’s freedom, the right of religious freedom, the importance of respecting religious freedom for the sake of peace, the role of the government in promoting religious freedom, and how the Church treats other religions.